Influence of Internal Workforce Diversity Factors on Labor Productivity in Construction Projects: Empirical Evidence from Pakistan - Maqsoom, A. (Institute of Electrical and Electronics Engineers Inc., 2020)
Workforce diversity is of immense importance as it has a direct relation with the employee and organizational performance. This idea delineates that organization should expedite and strive for the best in this competitive era. Across the globe, workforce diversity is viewed as a pre-requisite for successful ends. Organizations should see workforce diversity as their prime interest and use necessary resources for the benefit of workforce diversity, creating opportunities for employee performance. Various workforce diversity factors influence employee productivity, hence influencing the firm performance as well as the built environment. This research aims to analyze the motivation, technical skills, psychosocial and income related workforce diversity factors influencing labor productivity. Data was collected through on-site surveys. 131 usable responses were collected from the front-line workers and lower management professionals working at various construction project sites. Based on average Mean Importance Ranking (MIR) values, motivation and technical skill factors were identified as the most critical factors among the workforce diversity factors influencing the labor productivity. Also, it was identified that labor productivity is highly dependent on financial incentives, vocational training, technical skills for duties, good atmosphere, and good co-operation between team members. Â© 2020 IEEE.